EFEKTIVITAS BIMBINGAN PRA NIKAH DALAM MEMBENTUK KELUARGA SAKINAH MAWADAH WARAHAMAH (Studi di KUA Kec. Wonosalam Kab. Jombang) - Mohammad Arjati Firmansyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Pre-marital guidance is very important for prospective brides and grooms who want to get married, understanding the very broad meaning of household, the world of marriage is not only always pleasant, or the world of marriage does not only contain the desire to get married but also as a bridge for servants in worship. Of course, the question will be how to organize a good and correct marriage in creating a Sakinah family and which of course is in accordance with Islamic law, so with a pre-marital guidance program, it can help and guide prospective brides and grooms to solve or find out solutions to the problems they will face in domestic life. KUA as the organizer of the pre-marital guidance program is of course responsible for the sustainability of the pre-marital guidance program activities. The purpose of this research is to find out whether the implementation of the pre-marital guidance program in the Wonosalam District KUA is running smoothly and what efforts are being made by the KUA in Wonosalam District so that this pre-marital guidance program can run effectively and be able to have a good impact on candidates. bride and groom in living a domestic life, so that the prospective bride and groom have sufficient knowledge in dealing with domestic life.